The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/ijamh-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support and parental education as determinants of adolescents’ physical activity and eating behaviour: a cross-sectional survey

Abstract: Purpose: To examine the role of perceived social support and parental education on physical activity and eating behaviour of Ghanaian adolescents.Methods: Seven hundred and seventy Senior High School students (504 boys and 266 girls) between the ages of 14 to 21 years participated by completing questionnaires on perceived social support, physical activity and eating behaviour.Highest education attained by either parent or guardian was also obtained.Multivariate Analysis of Covariance was the main statistical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
2
24
0
1
Order By: Relevance
“…Upper middle Mixed 12-15 years (adolescent) 200 Multistage sampling, schools randomly selected from four educational zones of Mauritius and sample taken from three of these schools Glozah & Pevalin (37) Cross-sectional, self-reported questionnaires…”
Section: Mauritiusmentioning
confidence: 99%
See 1 more Smart Citation
“…Upper middle Mixed 12-15 years (adolescent) 200 Multistage sampling, schools randomly selected from four educational zones of Mauritius and sample taken from three of these schools Glozah & Pevalin (37) Cross-sectional, self-reported questionnaires…”
Section: Mauritiusmentioning
confidence: 99%
“…Qualitative and quantitative studies have found that the importance of household SES was apparent across a range of SES indicators including household income or wealth (23,24,33,43,50,54,57) , employment (32,43,45,56,57) , land ownership (43) and financial insecurity (22) . Educational level of individuals or parents was also found to play a role in dietary behaviours in several quantitative studies (30,33,37,(43)(44)(45)(46)52,54,56) . Higher parental education level was associated with better dietary intake in four quantitative studies among adolescents (30,33,37,46) , resulting in a higher modern dietary diversity score for adolescents in Tunisia, (30) higher household dietary diversity score in Ghana (33) and better healthy eating behaviours in Ghana (37) and Morocco (46) than those whose parents had average or low educational attainment.…”
Section: Mixed Adults; Female Adolescent Food Choicementioning
confidence: 99%
“…Highest education level of the parents has shown to have short-term and long-term effects on economic status, health, and well-being of the children (Dubow et al 2009). A single item on highest level of parental educational attainment has shown to predict effects on a wide range of social, psychological, physical, behavioral, and physiological health of children (Albrecht and Gordon-Larsen 2014;Peter and Sahn 2000;Glozah and Pevalin 2015;Marshall et al 2013;O'Toole and Wright 1991;Phillips et al 2009;Rok Simon et al 2016;Ross and Mirowsky 2011;Spera et al 2009;Vollmer et al 2017).…”
Section: Independent Variablementioning
confidence: 99%
“…From the perspective of all young individuals being both active and acted upon within their environmental contexts (Lerner and Overton, 2008), parents are presumed to impact significantly on their offspring's developmental processes, i.e., establishing physical activity behavior (McDavid et al, 2011;Gerard and Booth, 2015;Weiss and Phillips, 2015;Koning et al, 2016). Furthermore, parental influence, consisting of intangible (motivation and information) and tangible (instrumental and conditional) influential categories (Beets et al, 2010), as perceived by the adolescent, is revealed to be an important aspect of parental impact on adolescents' PA behavior (Glozah and Pevalin, 2015;. Applying a developmental perspective, Fredricks and Eccles (2004) suggest that parental influence differs according to developmental stage.…”
Section: Introductionmentioning
confidence: 99%